Improving balance control and self-reported lower extremity function in community-dwelling older adults: a randomized control trial. (March 2013) - Melzer, Itshak; Oddsson, Lars IE
Objectives: To evaluate the effect of a group-based functional and specific balance training programme that included dual-task exercises on balance function in healthy older adults. Design: A single-blind randomized controlled trial. Setting: General community. Participants: Sixty-six community-dwelling older adults (age 77.0 ± 6.5 years), without functional balance impairment were recruited and allocated at random to an intervention group ( n = 33) or a reference group ( n = 33). Intervention: The intervention group received 24 training sessions over three months that included perturbation as well as dual-task exercises. The reference group received no intervention. Outcome measures: The voluntary step execution times during single- and dual-task conditions, stabilogram-diffusion analysis in upright standing, and self-reported physical function; all were measured assessed at baseline and at the end of intervention. The intervention group was retested after six months. Results: Compared with the reference group, participation in group-based functional and specific balance training led to faster voluntary step execution times under single-task ( P = 0.02; effect size (ES) = 0.34) and dual-task ( P = 0.036; ES = 0.55) conditions; lower transition displacement and shorter transition time of the stabilogram-diffusion analysis under eyes-closed conditions ( P = 0.007, ES = 0.30 and P = 0.08, ES = 0.44, respectively); and improved self-reported lower extremity function ( P = 0.006, ES = 0.37). Effects were lost at six-month follow-up. Conclusions: Functional and specific balance training can improve voluntary stepping and balance control in healthy older non-fallers, parameters previously found to be related to increased risk of falls and injury in older adults.